KONFLIK SOSIAL DALAM PENGELOLAAN SUMBERDAYA HUTAN DI KPH RANDUBLATUNG - Novia Putri Puspitarani; Warsito .; Nunik Retno H (Journal of Politic and Government Studies, 2015)
Community Based Forest Resource Management (CBFM) is a system of forest management conducted jointly by the company and community, or the company and community with other interested parties (stakeholders) to share the soul, so that common interest to achieve sustainability of the functions and benefits of forest resources can be realized in an optimal and proportional. Along the way, the implementation of CBFM systems create conflict between the parties. The reason is because many stakeholders interested in the forest, while each of parties have many different needs and objectives. This research uses qualitative research methods with techniques of data collection through indepth interviews (depth interviews) and analysis of documentation. The results showed that the social conflict in Randublatung’s forest happened since colonial times untill this time is caused by some factors. Social conflict is caused by four factors: differences in perception, differences in interests (economic), changes in values and recognition of land ownership. Perhutani has done a variety of ways to resolve and reduce the conflict, such as socialization of CBFM, education and skills training, PLDT, providing support and so on. Based on the result, this research recommends some alternatives for conflict resolution, through a collaborative approach with open communication with the public space, management of forest resources are more participatory, improving the quality of human resources, and strengthening the management of organization.